Metro Manila street map (Mandaluyong City, Philippines : National Book Store, 2010)
"Certified by NAMRIA under certificate no. 2009-53 dated November 24, 2009."
Includes index.
Keywords: ROADS -- PHILIPPINES -- MANILA METROPOLITAN AREA -- MAPS